A study of the etiology and short term outcome of status epilepticus in children - Selvan, Tamil; V., Nagaraj M.; P., Saravanan; Tudu, Mrigender Nath (International Journal of Contemporary Pediatrics, 2017)
Background: Convulsive status epilepticus is the most common childhood medical neurological emergency, and is associated with significant morbidity and mortality. Most data for this disorder are from mainly adult populations and might not be relevant to childhood. This study was done to obtain a uniquely paediatric perspective. The objective of the study was to the etiology and short term outcome of patients admitted with status epilepticus between the age group 1 month to 12 years at a medical college hospital. Methods: Study design: Prospective descriptive study. Study Place: Department of Paediatrics, SIMS and RC, Bangalore, India. Study population: All children in the age group of 1 month to 12 years admitted with status epilepticus. Sample size:66. Study period: From January 2016 to December 2016. Results: Prevalence of status epilepticus among children admitted in this study was 8.7%. Most common age was found to be 1-3 years (54.5%). Preponderance of male (51.5%) over female (48.5%) was observed. The two most common etiology observed was Atypical febrile seizures (33.3%) and meningitis (22.7%). 57.5% children presented as first episode of seizure and duration of seizure was less than 2 hours in 65.1%. In our study, short term mortality rate was found to be 3% and morbidity was found to be 9% and meningitis was responsible for all the deaths. The mortality and morbidity in the form of neurodeficits were observed between the age group of 1 month to 3 years. Based on the duration of seizure lasting more than 8 hours, two third had mortality and one third had morbidity. Conclusions: Status epilepticus is a severe life threatening emergency with substantial morbidity and mortality. Major causes were due to atypical febrile seizure and meningitis. Patients with younger age, male sex and seizures lasting longer duration had higher mortality and morbidity, predicting the poor outcome.